2021
DOI: 10.1002/batt.202100145
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Pitfalls in Lithium Metal Battery Characterization

Abstract: Over the past decade, there has been a revival of research activity on lithium metal batteries (LMBs) as these could be a solution for key challenges of electromobility and the energy revolution. While there is growing consensus in the scientific community that common reporting standards and testing conditions for LMBs have to be established, a vast majority of research activities on lithium metal use lab‐dependant testing protocols. For that reason, this publication aims to shed light on various, potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Considering especially pouch cells, no standard and preferential position can be found as the best place always depends on the specific cell [9g] . However, it was found that the thickness change measured on the edges of the cell provided misleading information, as, for example, reduced expansion [9c,16b] or plating processes [9g,40] were found here. In addition, lateral expansions could also be translated into vertical expansions at the edges, if the electrode has a similar size than the cell body [11a] .…”
Section: Secondary Factors Influencing the Thickness Changementioning
confidence: 69%
“…Considering especially pouch cells, no standard and preferential position can be found as the best place always depends on the specific cell [9g] . However, it was found that the thickness change measured on the edges of the cell provided misleading information, as, for example, reduced expansion [9c,16b] or plating processes [9g,40] were found here. In addition, lateral expansions could also be translated into vertical expansions at the edges, if the electrode has a similar size than the cell body [11a] .…”
Section: Secondary Factors Influencing the Thickness Changementioning
confidence: 69%
“…The amount of electrolyte also significantly impacts the CE and cycling performance of LMBs and AFBs. , Half-cell Li∥Ni batteries containing 50 μL, 75 μL, and 100 μL electrolytes were prepared to verify the influence of the amount of electrolyte on the cyclability. As shown in Figure a, a larger amount of electrolyte results in a longer precycling procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of lithium CE is often affected by various factors, , and the electrochemical measurement methods reported in the literature often give different values, even for the same cell design. Few researchers have explicitly addressed the known parameters in determining the CE of LMBs and AFBs, as well as the trade-offs between CE and cycling reversibility. For example, Xiao et al discussed the fundamental definition of CE in various cell configurations (i.e., lithium-ion batteries, LMBs, and AFBs). They examined the comparisons between CE and capacity retention with different types and quantities of electrolytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the ether solvent system is characterised by a comparably low dielectric constant, which would, based on the previous work [65], suggest poorer cycling performance than in carbonates. Nevertheless, ether based systems are known to perform better for reversible lithium cycling than carbonate electrolytes [78], thus indicating that dielectric constants alone are not sufficient for prediction of cycling performance. In addition to that, when looking at the correlation graph for onset potential vs. dielectric constant (Supplementary Fig.…”
Section: Lithium Plating and Physical Electrolyte Propertiesmentioning
confidence: 99%